Perimenopausal Physical Activity and Dementia Risk: A Systematic Review - Simmons, Niall; Ruiz, Miguel Rodriguez; Ronca, Flaminia (International Journal of Sports Medicine, 2024)
Mixed-gender studies predominate in the current literature exploring the interaction between physical activity and dementia risk. Considering that menopause appears to contribute to females’ increased risk of cognitive decline when compared to males, further clarity is required on the impact of physical activity in reducing late-life dementia risk, specifically in perimenopausal females. A literature search of MEDLINE, EMBASE, Web of Science, SCOPUS and CINAHL databases yielded fourteen studies for review. A significant inverse relationship between perimenopausal leisure time physical activity, or physical fitness, and future all-cause dementia risk was found in most studies exploring this interaction. Higher levels of perimenopausal household physical activity and combined non-leisure time physical activity also displayed a favorable impact in lowering dementia risk. A dose-response effect was demonstrated, with approximately 10 MET-hour/week of leisure time physical activity required for significant dementia risk reduction. Three of four papers exploring causality provided analyses proposed to counter the reverse causation argument, suggesting that physical activity may indeed have a protective role in reducing dementia risk post-menopause. The current systematic review provides promising results regarding the impact of pre- and perimenopausal physical activity on reducing late-life dementia risk, suggesting that promoting perimenopausal physical activity may serve as a crucial tool in mitigating the risk of post-menopausal cognitive decline.
Keywords: dementia; leisure time physical activity; non-leisure time physical activity; systematic review; perimenopause